mmend98
  • mmend98
How can 1/3x – 2 = y and 1/4x + 11 = y be set up as a system of equations? 3y – x = –6 4y – x = 44 3y + x = –6 4y + x = 44 3y – 3x = –6 4y – 4x = 44 3y + 3x = –6 4y + 4x = 44
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
mmend98
  • mmend98
@ganeshie8
mmend98
  • mmend98
@Michele_Laino
anonymous
  • anonymous
convert them both to standard form.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Michele_Laino
  • Michele_Laino
for example, your first equation can be rewritten as follows: \[\frac{x}{3} - 2 = y \to x - 6 = 3y\] where I have multiplied both sides by 3
mmend98
  • mmend98
and thats all? @Michele_Laino @dirtydishr4g
Michele_Laino
  • Michele_Laino
yes! Please multiply the both sides of your second equation by 4, what do you get?
Michele_Laino
  • Michele_Laino
Hint: you should get this: \[\frac{x}{4} + 11 = y \to x + 44 = 4y\]
mmend98
  • mmend98
I get x+44=4y
mmend98
  • mmend98
@Michele_Laino
Michele_Laino
  • Michele_Laino
that's right!
Michele_Laino
  • Michele_Laino
now, if I subtract x, I get: \[x + 44 - x = 4y - x\] please simplify
mmend98
  • mmend98
4y-x=44? @Michele_Laino
Michele_Laino
  • Michele_Laino
that's right!
Michele_Laino
  • Michele_Laino
now I do the same with your first equation: \[x - 6 - x = 3y - x\] please simplify
mmend98
  • mmend98
So the answer would be A? 3y – x = –6 4y – x = 44
Michele_Laino
  • Michele_Laino
that's right!
mmend98
  • mmend98
Thank you. @Michele_Laino
Michele_Laino
  • Michele_Laino
:)

Looking for something else?

Not the answer you are looking for? Search for more explanations.